Efficacy of injections of phosphatidylcholine into fat deposits-a non-surgical alternative to liposuction in body-contouring - Heinrich, Karl G (Indian Journal of Plastic Surgery, 2005)
Injecting phosphatidylcholine has been used in South America as a non-surgical treatment in body contouring. The objective of this study was to demonstrate the efficacy of injecting phosphatidylcholine in the reduction of localised fat deposits. 86 patients were included in the study. Patients received 1-3 treatments in localised fat deposits in various areas of the body using phosphatidylcholine. After treatment with phosphatidylcholine (250 mg / 5 ml), fat deposits show an average circumferential reduction per application of 2.70 cm. No patient showed irregularities, dimples or any serious side effect after treatment. Results remained stable during the time of follow up. All patients showed remarkable reductions of the fat deposits treated with phosphatidylcholine. Using the correct technique, injecting phosphatidylcholine may be a safe and efficacious alternative to liposuction in patients objecting to surgery.
Keywords: Injection lipolysis; Fat-away-injection; Lipostabil; Phosphatidylcholine; Liposuction; Microcannula; Cosmetic surgery.